Apakah Edukasi dengan Video Animasi Efektif terhadap Pengetahuan Remaja mengenai Perkawinan Anak? - Komara, Tania Ghifari; Yulinda, Yulinda; Hidayanti, Desi; Ulfah, Kurniaty (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2026)
Background: This study aims to examine the effectiveness of animated video education on adolescents' knowledge about child marriage in Rancakasumba Village, Bandung Regency, Indonesia. Method: The study used a quantitative approach with a quasi-experimental, non-randomized control group pretest-posttest design. Statistical analysis employed Mann-Whitney test for age distribution, Fisher's Exact Test for gender distribution, Chi-Square test for educational background, and Marginal Homogeneity test for pre-post intervention comparisons. The study population was adolescents in Rancakasumba Village, Bandung Regency, with a sample of 60 respondents divided into an experimental group (animated video) and a control group (leaflet). The research instrument was a structured questionnaire containing 29 questions that had been validated with a Cronbach's Alpha reliability value of 0.936. The animated video was developed collaboratively with health promotion students and validated by multimedia experts, while the leaflet contained equivalent educational content for the control group. Result: The study showed that the animated video was more effective than the leaflet in increasing adolescents' knowledge about child marriage. The experimental group experienced an increase in knowledge, from 36.7% to 90% (p-value 0.001), while the control group only increased from 20% to 26.7% (p-value 0.025). Comparison between groups after the intervention showed a significant difference with a p-value of 0.028. Implication: Healthcare professionals and policymakers should integrate animated video technology into routine reproductive health education programs to achieve optimal outcomes in preventing child marriage. Novelty: This study comprehensively analyzes the effectiveness of animated videos using a quasi-experimental design that controls for confounding variables within the specific geographic and sociocultural context.